The Aesthetics of Detail in Nizar Qabbani’s Poetry (Journal of Imam Al-Kadhim College, 2026)
Postmodern poetry emerged with a different current that challenged traditional poetry in both form and content. Postmodern poetry has focused on small and precise details—details that were marginalized in classical poetry— as the modern poet made intensive use of minor elements through everyday language and simple details. This approach gives the reader a stronger sense of realism compared to traditional poetry, and Nizar Qabbani is considered one of the pioneers of this trend in most of his poetic works.
Keywords: Poetry; Postmodernism; Nizar Qabbani; Detailism